2023
DOI: 10.3389/fpsyt.2023.1229439
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone, an opioid like the others?

Nicolas Marie,
Florence Noble

Abstract: The over-prescription of opioid analgesics is a growing problem in the field of addiction, which has reached epidemic-like proportions in North America. Over the past decade, oxycodone has gained attention as the leading opioid responsible for the North America opioid crisis. Oxycodone is the most incriminated drug in the early years of the epidemic of opioid use disorder in USA (roughly 1999–2016). The number of preclinical articles on oxycodone is rapidly increasing. Several publications have already compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 122 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…As one of the most commonly used opioids for treating acute and chronic pain, oxycodone is a relatively selective MOR agonist; it can also bind to KOR and DOR with very low affinity, in the μM range ( Peckham and Traynor, 2006 ; Marie and Noble, 2023 ). Zhang et al (2017) observed significant changes in the expression of genes associated with inflammation and immune function upon oxycodone administration, supporting its link to inflammation and immune response.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most commonly used opioids for treating acute and chronic pain, oxycodone is a relatively selective MOR agonist; it can also bind to KOR and DOR with very low affinity, in the μM range ( Peckham and Traynor, 2006 ; Marie and Noble, 2023 ). Zhang et al (2017) observed significant changes in the expression of genes associated with inflammation and immune function upon oxycodone administration, supporting its link to inflammation and immune response.…”
Section: Introductionmentioning
confidence: 99%